Anterior meniscus extrusion is associated with anterior tibial osteophyte width in knee osteoarthritis – The Bunkyo Health Study - Adili, Arepati; Kaneko, Haruka; Aoki, Takako; Liu, Lizu; Negishi, Yoshifumi; Tomura, Jun; Wakana, Suguru; Momoeda, Masahiro; Arita, Hitoshi; Hada, Shinnosuke; Shiozawa, Jun; Kubota, Mitsuaki; et al. (Osteoarthritis and cartilage open, 2023)
In knee osteoarthritis (OA), medial meniscus extrudes both medially and anteriorly. We reported that full-length width of medial tibial osteophyte, which comprises cartilage and bone parts, is directly associated with medial meniscus extrusion in early-stage knee OA and hypothesized that anterior tibial osteophyte (ATO) is also associated with anterior meniscus extrusion (AME). Thus, we aimed to examine their prevalence and relationship. Elderly subjects (638 females and 507 males; average 72.9 years old) in the Bunkyo Health Study cohort were enrolled. MRI-detected OA changes were evaluated according to the Whole Organ Magnetic Resonance Imaging Score. ATO was evaluated using the method which can assess both cartilage and bone parts of osteophyte by pseudo-coloring images of proton density-weighted fat-suppressed MRI. Most subjects showed the Kellgren-Lawrence grade 1/2 of the medial knee OA (88.1%), AME (94.3%, 3.7 ​± ​2.2 ​mm), and ATO (99.6%, 4.2 ​± ​1.5 ​mm). Among the OA changes, AME was most closely associated with full-length width of ATO (multivariable β ​= ​0.877, p ​< ​0.001). The area under the receiver operating characteristic curve for determining the presence of AME as evaluated by ATO width was 0.75 (95% confidence interval 0.60–0.84, p ​< ​0.001). The odds ratio for the presence of AME as evaluated by ATO width at 2.9 ​mm was 7.16 (4.23–12.15, p ​< ​0.001, age, gender, BMI, and K-L adjusted). AME and ATO were inevitably observed in the elderly subjects and AME was closely associated with full-length width of ATO. Our study provides the first evidence on the close relationship between AME and ATO in knee OA.